2019
DOI: 10.1371/journal.pntd.0007221
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, ecology and human perceptions of snakebites in a savanna community of northern Ghana

Abstract: Background Worldwide, snakebite envenomations total ~2.7 million reported cases annually with ~100,000 fatalities. Since 2009, snakebite envenomation has intermittently been classified as a very important ‘neglected tropical disease’ by the World Health Organisation. Despite this emerging awareness, limited efforts have been geared towards addressing the serious public health implications of snakebites, particularly in sub-Saharan Africa, where baseline epidemiological and ecological data remain i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 49 publications
4
44
0
1
Order By: Relevance
“…Identifying and testing the general patterns between ecological factors and venom functionality and composition at large taxonomic scales can offer a key pathway to understanding the fundamental mechanisms driving the evolution of venom diversity. Ultimately, understanding such mechanisms may contribute to clinical developments [12,54] and aid in bioprospecting [5,55]. From an ecological perspective, understanding the association between diet and venom may aid in our ability to predict the ecological role of venomous predators in rapidly changing ecosystems [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying and testing the general patterns between ecological factors and venom functionality and composition at large taxonomic scales can offer a key pathway to understanding the fundamental mechanisms driving the evolution of venom diversity. Ultimately, understanding such mechanisms may contribute to clinical developments [12,54] and aid in bioprospecting [5,55]. From an ecological perspective, understanding the association between diet and venom may aid in our ability to predict the ecological role of venomous predators in rapidly changing ecosystems [56].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the potential invasiveness of certain venomous species may be mediated by the prey specificity of their venoms, with species with generalist venoms, such as the highly invasive Brown widow (Latrodectus geometricus) and the Noble false widow (Steatoda nobilis), more likely to have venoms which can functionally take advantage of novel prey items [57,58]. Developing clear ecological and evolutionary predictions regarding the composition and functionality of venoms across the animal kingdom can not only offer pathways to understanding nature's complex cocktails, but may also aid in to our ability to manage future medical [5,54,55] and ecological issues relating to venom [5].…”
Section: Discussionmentioning
confidence: 99%
“…The rural poor in Sub-Saharan Africa, South Asia and South-East Asia are disproportionally affected, as the most venomous snakes coexist with them in the areas they live and work in [5,8,9]. Bites are incurred most frequently by young and economically active members of communities aged 15-50 years [5,10] and are most often localized on the extremities [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, a TH might serve an average population of 400 individuals [21] whereas the ratio of university-trained physicians to population is only approximately 1.2/10 000 with significant interregional variation [22]. A household survey in northern Ghana showed that THs tend to nearly half of all snakebite victims in the community [10], a finding similar to a survey of snakebite victims in Sri Lanka, which showed that 43% of victims first sought aid from a TH [18].…”
Section: Introductionmentioning
confidence: 99%
“…Snakebites have become an event which claims the lives of between 81,000 and 138,000 persons annually most of whom are poor persons in developing countries involved in agriculture to produce food for their nations and for export to bring foreign exchange to their countries [4]. Although some victims of snake bites seek the services of traditional healers many others seek medical assistance from orthodox health facilities where provision of quality healthcare service can ensure the survival of a snakebite victim or eliminate or reduce any post exposure morbidity [6,11].…”
Section: Discussionmentioning
confidence: 99%